2005
DOI: 10.1152/japplphysiol.00294.2004
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in knee extension power, contractile velocity, and fatigability

Abstract: The purposes of this study were to examine age and gender differences in knee extensor strength, power, and fatigue using open- and closed-chain testing procedures. We tested the hypothesis that specific strength (strength/unit muscle mass) would not differ by age, whereas age differences in specific power and fatigue would remain consequent to blunted maximal contractile velocity. Skeletal muscle performance was examined in 28 young (26.9 +/- 0.7 yr) and 24 older (63.6 +/- 0.8 yr) men and women. Assessments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
222
2
9

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(250 citation statements)
references
References 46 publications
17
222
2
9
Order By: Relevance
“…However, the slower walking speed chosen by the elderly subjects might be also dependent on weakness of the quadriceps muscles caused by aging (Norris et al, 2007;Tiedemann et al, 2005). As noted before, the number of fast twitch fibers decreases with aging (Lexell et al, 1988;Petrella et al, 2005). If the quadriceps muscle is weakened and/or the number of fast twitch fibers of the quadriceps muscles is decreased or vice versa, then the risk of falling, which can cause serious injury, is increased.…”
Section: Walkingmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the slower walking speed chosen by the elderly subjects might be also dependent on weakness of the quadriceps muscles caused by aging (Norris et al, 2007;Tiedemann et al, 2005). As noted before, the number of fast twitch fibers decreases with aging (Lexell et al, 1988;Petrella et al, 2005). If the quadriceps muscle is weakened and/or the number of fast twitch fibers of the quadriceps muscles is decreased or vice versa, then the risk of falling, which can cause serious injury, is increased.…”
Section: Walkingmentioning
confidence: 98%
“…Some previous studies indicated that a systematic decrease in the number of fast twitch fibers of the quadriceps muscles 68 Biomechanical Analysis of Gait and STS occurred with an association of aging (Lexell et al, 1988;Petrella et al, 2005). If the number of fast twitch fibers of the quadriceps muscles was decreased, then the dynamic postural stability would also be decreased because the sensorimotor function would be slowed in these muscles (Lord et al, 1996).…”
Section: Stsmentioning
confidence: 98%
See 1 more Smart Citation
“…A perda da potência muscular é maior que a da força devido à perda seletiva das fibras tipo II (fibras de contração rápida). A diminuição da potência muscular determina diminuição da velocidade de contração muscular e esta perda nos músculos responsáveis pela manutenção da postura ortostática pode contribuir para o aumento do número de quedas (19) . Neurologicamente, existe diminuição, eventualmente modulada por sinais aferentes das articulações comprometidas (inibição artrogênica), do número e do tamanho das unidades motoras e isso é também uma causa primária da perda da força muscular (20) .…”
Section: Efeitos Fisiológicos Do Envelhecimentounclassified
“…This is caused by suppressed formation of humoral factors that stimulate protein synthesis, with the simultaneous expression of subclinical inflammation factors (TNf-α, IL-6) and a decline in myocyte apoptosis [28,29].…”
mentioning
confidence: 99%